PENGEMBANGAN METODE DISKUSI BERMUATAN PRESENTASI SISTEM ROTASI PADA MATA KULIAH PROGRAM LINIER BERBASIS KEARIFAN LOKAL - Ali, Ferdinandus Ardian; Mulu, Hildegardis (IKIP Siliwangi, 2020)
This Research aims to produce a discussion method containing the presentation of a rotational system in linear program courses based on local wisdom that meets the eligibility requirements (Valid, Practical, and Effective). Development steps, namely; define, design, develop, and disseminate. Testing the use of discussion method containing the presentation of the rotation system on the linear program based on local wisdom was carried out on students of the Indonesian Catholic University (UNIKA) Mathematics Education Study Program, Santu Paulus Ruteng, class of 2019. The instruments used were interviews, tests, and questionnaires. Interviews were conducted to find out an initial description of the research problem. Tests are given to determine the level of effectiveness. The questionnaire was used to determine the level of validity and level of practicality. The validity questionnaire was given to 2 experts in the field of mathematics education, while the practicality questionnaire was given to students. Research result shows that, the discussion method containing the presentation of the rotation system on the linear program based on local wisdom that has been developed is declared feasible (Valid, Practical, and Effective). Through this method, each student is active during the learning process. The activeness of each student occurs, when entering the presentation stage of the rotation system (presentations are carried out alternately between one student and another) in internal groups and external groups.